Performance evaluation of wearable antenna printed using syringe-based deposition system on fabric. (August 2019) - Khirotdin, R K; Mahadzir, M A; Seman, F C; Dahlan, S H; Hassan, N
Abstract: Wearable antenna is recently known as part of clothing for communication purposes. Syringe-based deposition system had been proven capable of printing functional antenna structure but the printed antenna performances have not been discussed in details especially on resisting bending under various angles, curvature radiuses and wet conditions. Hence, this paper discusses the performance of printed antenna under various bending angles, curvature radiuses and wet conditions. The effect of several bending angles, curvature radiuses and wet conditions on resonance frequency, return loss and radiation pattern were discussed and compared accordingly with simulation. The antennas were observed to resonate best at frequency of 1.571 GHz as expected and the return loss obtained was at -20 dB that is 30% more than simulation which offers better performance. The radiation pattern obtained was as predicted since larger magnitude for the main lobe was produced than the side lobe. The antenna exhibited exceptional elasticity as it resists bending up to 30° angle and 5 cm of vertical convex curvature radius. Polyester fabric performed as a good candidate for textile wearable applications and water had only minor effect on antenna performance makes the proposed antenna suitable for humid condition.